SQLServer Megaservers: Scalability, Availability, Manageability - Gray, Jim; Waymire, Richard (2003)
This is an update to the 1997 report Jim Gray wrote on SQL Server scalability. It is a marketing whitepaper. Microsoft® SQL Server™ has evolved to support huge databases and applications, including multiterabyte databases used by millions of people. SQL Server achieves this scalability by supporting scale up on symmetric multiprocessor (SMP) systems, allowing users to add processors, memory, disks and networking to build a large single node, as well as scale out on multinode clusters, allowing a huge database to be partitioned into a cluster of servers, each server storing part of the whole database, and each doing a part of the work, while the database remains accessible as a single entity. Using scale out, SQL Server 2000 achieved the top Transaction Processing Council Benchmark C (TPC-C) performance results of any database system on any platform. .NET servers and SQL Server clusters provide high availability and automated management. SQL Server supports high availability through built-in failover and replication technologies. SQL Server also provides a powerful management model based on a user interface, wizards, a job scheduler for repetitive tasks, and SQL-DMO for scripting application-specific operations. SQL Server architecture accommodates modular growth, automated configuration, maintenance, and programming of large server farms.